2022
DOI: 10.1021/acsami.2c00828
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Links–Entanglements Integrated Networks Contributing to Highly Resilient, Soft, and Self-Adhesive Elastomers with Low Hysteresis for Green Wearable Electronics

Abstract: Green wearable electronics are attracting increasing attention to eliminate harmful byproducts generated by traditional devices. Although various degradable materials have been explored for green wearable electronics, the development of degradable elastomers with integrated characteristics of low modulus, self-adhesion, high resilient, and low hysteresis remains challenging. In this work, a degradable elastomer poly­(1,8-octanediol-co-citrate-co-caprolactone) (POCL) is reported, in which a loosely cross-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…7 Mechanical strength reinforcement by fibrous fillers through physical entanglement. 117 TS, tear strength, and hardness increased with increasing ller content, whereas EB increased only slightly at a certain ller concentration before decreasing at higher ller loading. The inverse reinforcement between TS and EB was also seen in most conventional synthetic rubber llers such as carbon black, silica, and clay materials.…”
Section: Bio-based Llers In Synthetic Rubbersmentioning
confidence: 89%
“…7 Mechanical strength reinforcement by fibrous fillers through physical entanglement. 117 TS, tear strength, and hardness increased with increasing ller content, whereas EB increased only slightly at a certain ller concentration before decreasing at higher ller loading. The inverse reinforcement between TS and EB was also seen in most conventional synthetic rubber llers such as carbon black, silica, and clay materials.…”
Section: Bio-based Llers In Synthetic Rubbersmentioning
confidence: 89%
“…In this system, however, the manipulation became challenging and fatigue life got limited because of the POMAC’s sticky gel nature. By using poly­(1,8-octanediol- co -citrate- co -caprolactone), the sticky gel aspect was improved, but the gel contents showed that the majority of PCL is not in the crosslinked network, which may impart stability issues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electronic waste (e-waste) has emerged as a serious contamination problem in the environment. This is because of the rapid development in electronics technology, short lifetime of electronic devices, and high recycling cost. Furthermore, discarded e-waste may lead to the release of large toxic elements, including heavy metals and hazardous chemicals, which could eventually enter the biological system via soil, water, and human food chains. , To address this problem of e-waste, a promising strategy is to develop “green” electronic devices based on biodegradable or renewable polymers. Interestingly, green flexible electronic devices, which comprise biodegradable celluloses, have garnered considerable attention for a variety of applications since cellulose is an abundant, low-cost, and sustainable material. Many laboratories, including ours, have been dedicated to the development of various conductive composites based on cellulose for green electronics, to retain conductivity and introduce environmental friendliness and facile recycling/disposal. …”
Section: Introductionmentioning
confidence: 99%
“…7−9 Furthermore, discarded e-waste may lead to the release of large toxic elements, including heavy metals and hazardous chemicals, which could eventually enter the biological system via soil, water, and human food chains. 10,11 To address this problem of e-waste, a promising strategy is to develop "green" electronic devices based on biodegradable or renewable polymers. Interestingly, green flexible electronic devices, which comprise biodegradable celluloses, have garnered considerable attention for a variety of applications since cellulose is an abundant, low-cost, and sustainable material.…”
Section: Introductionmentioning
confidence: 99%